Penggunaan Media Sosial Instagram Sebagai Sarana Promosi Bagi UMKM Limunite di Kelurahan Sukorejo Kota Blitar - Regita Endah Cahyaning Naya; Ririn Putri Anggraeni; Fadilah Rizqi Muhamad; Gideon Setyo Budiwitjaksono (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study aims to observe the use of Instagram social media as a promotional means for MSME Limunite in the village of Sukorejo City of Blitar. The research method used is qualitative, involving Limunite MSMEs. Data collected through interviews and observations. The results of this study indicate that the social media of the Instagram can be an effective promotion of that MSMEs. Through social media Instagram This Limunite MSMEs can expand its sales by making visual content such as photo products and promotional videos that can increase sales. The conclusion of this study is the use of Instagram social media as a promotion of facilities for MSMEs Limunite in the Sukorejo has a great opportunity by using promotion.